2023
DOI: 10.1021/acsami.3c09573
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-Responsive Sequentially Targeted AIE Fluorescent Probe for Precisely Identifying the Atherosclerotic Plaques

Jie Liu,
Zhigui He,
Yuan Zhong
et al.

Abstract: The formation of atherosclerosis is the root cause of various cardiovascular diseases (CVDs). Therefore, effective CVD interventions call for precise identification of the plaques to aid in clinical treatment of such diseases. Herein, a reactive oxygen species (ROS)-responsive sequentially targeted fluorescent probe is developed for atherosclerotic plaque recognition. An aggregation-induced emission active fluorophore is linked to maleimide (polyethylene glycol) hydroxyl with a ROS-responsive cleavable bond, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…The experimental results showed that the pH in the blood and tissues of the mice in the early-stage of atherosclerosis was lower than that of control mice, while the phosphate and phosphorylation levels were higher than those of the control mice. Soon afterwards, Liu and colleagues 73 developed a sequence-responsive fluorescent probe (TPAMCF) for ROS and LDs. TPAMCF has high affinity for phosphatidylserine externalization of foam cells through its CLIKKPF peptide structure.…”
Section: Fluorescence Imaging Of Atherosclerosismentioning
confidence: 99%
“…The experimental results showed that the pH in the blood and tissues of the mice in the early-stage of atherosclerosis was lower than that of control mice, while the phosphate and phosphorylation levels were higher than those of the control mice. Soon afterwards, Liu and colleagues 73 developed a sequence-responsive fluorescent probe (TPAMCF) for ROS and LDs. TPAMCF has high affinity for phosphatidylserine externalization of foam cells through its CLIKKPF peptide structure.…”
Section: Fluorescence Imaging Of Atherosclerosismentioning
confidence: 99%